Praktik Pesta Rondang Bittang dalam Masyarakat Islam di Kabupaten Simalungun - Nuralam, Laode Moh. (UIN Sumatera Utara, 2024)
This study is a qualitative study that aims to determine the response of the Muslim community regarding the Rondang Bittang Festival in Simalungun Regency. This study was motivated by the existence of an animist ritual in the practice of the Rondang Bittang party. Data collection using observation, interview and documentation methods. And the results of this study were analyzed using descriptive analysis methods. The results of this study show the existence and practice of the Rondang Bittang Party which still contains ritual offerings to the spirits of the rulers of nature (panghulu balang). Then the role of Islam is reviewed from the aspect of the values of Aqidah in the ritual and the response of the Muslim community to the animist ritual contained in the practice of the Rondang Bittang Party. Based on this study, the Rondang Bittang Party is one example of a form of gratitude that exists in culture. Different from the form of gratitude carried out in a religion, especially Islam. The essence of gratitude in Islam is to acknowledge the blessings of Allah because He is the owner of gifts and gifts so that the heart acknowledges that all blessings come from Allah SWT. Then his limbs submit to the giver of the blessing. What is called submission is obeying and being obedient because someone is not called submission, unless he obeys Allah's command and obeys His sharia. To the Simalungun community who always carry out the Rondang Biitang party tradition, they must always maintain the ties of friendship and continue to preserve what is characteristic of the Simalungun community without damaging the faith and morals in religion.